تیۆری هەڵوەشاندنەوە لە دەقی شیعریدا - محمد, عبدالقادر حمە أمین; قادر, ئاوارە فەرەیدون (Sulaimani Journal for Humanities, 2018)
To work on a certain text from a general point of view and at the same time following a certain literary approach is not an easy task. There are some reasons for this. First, the text should be selected based on certain criteria. Secondly, it should be analyzed in connection to the philosophical/ literary approach chosen by the critic/ researcher. Sometimes, analyzing the views of the founder of the literary approach makes the task more challenging. The elements of deconstruction that are used to analyze texts are some significant elements. Jacques Derrida, the founder of this literary approach, has successfully made his theory a modern one and he has given it enough recognition that the theory is now widely used to tackle and analyze various texts. In todays literary world, deconstruction is of so much significance and is one of the frequently practiced approaches to understand texts. What distinguishes deconstruction is that it provides the critic with new insights to approach texts and analyze them; in other words, deconstruction attempts to present a new and genuine explanation to the contexts it tackles.